Efeitos da alta demanda inspiratória no equilíbrio e índice de risco de queda em idosos - Pereira, Thalles Andrade Marques [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
Introduction: Aging can promote physiological and functional changes that lead to declines in functional capacity, influencing autonomy, joint mobility and inspiratory muscle deficiency, which negatively interferes with postural stability and increases the risk of falling. Objectives: To analyze the effect of high inspiratory demand on balance and risk of falling in the elderly. Methodology: Thirteen elderly men (73 ± 7.25 years) were selected in whom the maximum inspiratory pressure (PImax) was evaluated. Then, the participants performed the Postural Stability Test (PST) and Modified Clinical Test of Sensory Interaction and Balance (m-CTSIB) on the Biodex Balance System (BBS) platform with increased respiratory demand and immediately after the tests. PST and m-CTSIB were performed under three conditions: baseline assessment with free breathing; with an increase in the inspiratory demand (the elderly person breathed through the POWER Breathe Plus HR® equipment with a resistance of 50% of their MIP obtained before the test was performed) and final assessment (immediately after the end of the test with an increase in the inspiratory demand). The conditions analyzed in the m-CTSIB were Eyes Open Firm Surface (EOFS), Eyes Closed Firm Surface (ECFM), Eyes Open Foam Surface (EOFOS) and Eyes Closed Foam Surface (ECFOS). For data analysis, the Shapiro-Wilk and Homogeneity tests were performed using the Levene test, and the One-way Analysis of Variance for repeated measures (ANOVA). All analyzes were performed using SPSS 21.0 adopting p<0.05. Results: In the PST, the values for the stability index were similar in all analyzed variables. In the CTSIB protocol, the pre and during comparison showed significant differences in the EOFS conditions (Pre: 1.03 ± 0.53 and During: 1.70 ± 0.57 with p=0.003), EOFOS (Pre: 1.73 ± 0.50 and During: 3.08 ± 0.80 with p=0.000) and in Fall Risk (Pre: 2.39 ± 0.57 and During: 3.09 ± 0.72 with p=0.001). When these conditions were compared during and after the tests, there were significant differences in all conditions analyzed, namely: EOFS (During: 1.70 ± 0.57 and After: 1.00 ± 0.33 with p=0.000 ), ECFS (During: 1.91 ± 0.75 and After: 1.48 ± 0.54 with p=0.001), EOFOS (During: 3.08 ± 0.80 and After: 2.08 ± 1.24 with p=0.007), ECFOS (During: 5.63 ± 1.80 and After: 4.43 ± 1.25 with p=0.004) and Fall Risk (During: 3.09 ± 0.72 and After: 2, 25 ± 0.57 with p=0.000). And finally, when pre and after were compared, only the ECFOS condition showed a significant difference (Pre: 5.09 ± 1.3 and After: 4.43 ± 1.3 with p=0.040). Conclusions: It is concluded that the overload in the inspiratory demand was able to 9 cause changes in the balance variables, especially when the volunteer is exposed to overload, causing a quick recovery in the period after. The risk of falling was increased with the use of inspiratory overload, which suggests attention to balance in the elderly when inspiratory exercises are prescribed.

Introdução: O envelhecimento pode promover alterações fisiológicas e funcionais que acarretam declínios da capacidade funcional, influenciando na autonomia, mobilidade articular e na deficiência muscular inspiratória o que interfere negativamente na estabilidade postural e no aumento do risco de queda. Objetivos: Analisar o efeito da alta demanda inspiratória no equilíbrio e risco de queda em idosos. Metodologia: Foram selecionados 13 homens idosos (73 ± 7,25 anos) nos quais a Pressão Inspiratória máxima (PImáx) foi avaliada. Em seguida, os participantes realizaram os testes Postural Stability Test (PST) e Modified Clinical Test of Sensory Interaction and Balance (m-CTSIB) na plataforma Biodex Balance System (BBS) com incremento da demanda respiratória e imediatamente após os testes. O PST e m-CTSIB foram realizados em três condições: avaliação inicial com respiração livre; com um incremento da demanda inspiratória (o idoso respirava por meio do equipamento POWER Breathe Plus HR® com resistência de 50% de sua PImáx obtida previamente a realização do teste) e avaliação final (imediatamente após a finalização do teste com incremento da demanda inspiratória). As condições analisadas no m-CTSIB foram Eyes Open Firm Surface (EOFS), Eyes Closed Firm Surface (ECFM), Eyes Open Foam Surface (EOFOS) e Eyes Closed Foam Surface (ECFOS). Para análise dos dados, foram realizados os testes de Shapiro-Wilk e da Homogeneidade pelo teste de Levene, e a análise de Variância One-way para medidas repetidas (ANOVA). Todas as análises foram realizadas no SPSS 21.0 adotando p<0,05. Resultados: No PST, os valores para o índice de estabilidade foram similares em todas as variáveis analisadas. No protocolo CTSIB, a comparação pré e durante, demonstrou diferenças significativas nas condições EOFS (Pré: 1,03 ± 0,53 e Durante: 1,70 ± 0,57 com p=0,003), EOFOS (Pré: 1,73 ± 0,50 e Durante: 3,08 ± 0,80 com p=0,000) e no Fall Risk (Pré: 2,39 ± 0,57 e Durante: 3,09 ± 0,72 com p=0,001). Quando estas condições foram comparadas durante e após a realização dos testes, ocorreram diferenças significativas em todas as condições analisadas, a saber: EOFS (Durante: 1,70 ± 0,57 e Após: 1,00 ± 0,33 com p=0,000), ECFS (Durante: 1,91 ± 0,75 e Após: 1,48 ± 0,54 com p=0,001), EOFOS(Durante: 3,08 ± 0,80 e Após: 2,08 ± 1,24 com p=0,007), ECFOS (Durante: 5,63 ± 1,80 e Após: 4,43 ± 1,25 com p=0,004) e Fall Risk (Durante: 3,09 ± 0,72 e Após: 2,25 ± 0,57 com p=0,000). E por fim, quando pré e após foram comparados, apenas a condição ECFOS demonstrou diferença significativa (Pré: 5,09 ± 1,3 e Após: 4,43 ± 1,3 com p=0,040). Conclusões: Conclui-se que a sobrecarga na demanda inspiratória foi capaz de causar alterações nas variáveis de equilíbrio, principalmente quando o voluntário é exposto a sobrecarga, causando uma rápida recuperação no período após. O risco de queda foi aumentado com o uso da sobrecarga inspiratória, o que sugere atenção sobre o equilíbrio em idosos quando exercícios inspiratórios são prescritos.
Effects of high inspiration demand on balance and fall risk index in elderly
Keywords: Biodex Balance System; Breathing; Elderly; Biomechanics; Idosos; Respiração